Resolving Africa's multilateral debt problem : a response to the IMF and the World Bank - Mistry, Percy S. (FONDAD The HagueNL, 1996)
Takes a detailed look at the figures and policies behind the multilateral debt crisis. Suggests that there should be a new strategy to resolve the crisis.